Riboflavin along with antibiotics balances reactive oxygen species and inflammatory cytokines and controls Staphylococcus aureus infection by boosting murine macrophage function and regulates inflammation. Issue 1 (December 2016) - Dey, Somrita; Bishayi, Biswadev
Abstract Background Macrophages serve as intracellular reservoirs ofS. aureus . Recent in vitro studies have confirmed high level resistance byS. aureus to macrophage mediated killing and the intracellular persistence of Staphylococci may play an important role in the pathogenesis. Since this localization protects them from both cell-mediated and humoral immune responses, therefore, a successful anti-staphylococcal therapy should include the elimination of intracellular bacteria, further protecting the host cells from staphylococci-induced cell death. So, only antibiotic therapy may not be helpful, successful therapy needs combination of drugs not only for elimination of pathogen but also for rescuing the host cell forS. aureus induced cell death. Methods In keeping with this idea an in vitro study has been done to examine the effect of Riboflavin along with antibiotics on phagocytosis, hydorgen peroxide, superoxide production, antioxidant enzyme levels, and cytokine levels in mouse macrophages for amelioration of theStaphylococcus aureus burden. The immune boosting effects of Riboflavin have been validated through perturbations of redox homeostasis and pro-inflammatory cytokines measurements. Results It was observed that the supplementation of Vitamin B-2 (Riboflavin) not only enhances macrophage function as previously reported but also decreases pro-inflammatory responses inStaphylococcus aureus infected macrophages. The observed influence of Riboflavin on enhanced antimicrobial effects such as enhanced phagocytosis of macrophages exposed toS. aureus, hydrogen peroxide or superoxide production when combined with either ciprofloxacin (CIP) or Azithromycin (AZM) and decrease in pro-inflammatory responses of IFN-γ, IL-6, IL-1β. Riboflavin treatment also decreased NO and TNF-α level possibly by inhibiting the NF-κβ pathway. The increased antioxidant enzymes like glutathione reductase, SOD and GSH level helped in maintaining a stable redox state in the cell. Conclusion Riboflavin plus antibiotic pretreatment not only enhances macrophage functions but also decreases proinflammatory responses inStaphylococcus aureus infected macrophages indicating better bacterial clearance and regulated inflammation which may be considered as a novel and important therapeutic intervention.